4D BIM models for smart utility relocation management in urban infrastructure projects. Issue 1 (19th October 2020) - Vilventhan, Aneetha; Razin, Sanu; Rajadurai, R.
Abstract : Purpose: The relocation of existing underground utilities in urban environments is complex because of the existence of multiple utility agencies being responsible for numerous utilities and over constrained space and time to execute maintenance works. Unfamiliar location and insufficient records of maintenance data hamper the flow of work, causing unnecessary delays and conflicts. The aim of the paper is to explore 4 dimensional Building Information Modeling as a smart solution for the management of multiple utility data for a relocation project in an urban setting. Design/methodology/approach: An empirical case-based research methodology is used to collect data and develop the BIM models. Two ongoing construction projects in an urban city are empirically studied, and 4D BIM models of identified utilities are developed to assist management and relocation of existing utilities. Findings: The developed BIM models enabled the location of existing sub-surface utilities through 3D visualization and also enabled clash detection. The 4D simulation of BIM model enabled the tracking of actual progress of relocation works and thereby helped in taking necessary actions to minimize forthcoming delays. The evaluation of the developed model showed that the application of 4D BIM improved communication and coordination during utility relocation works. Practical implications: 4D BIM for utility infrastructure provides better management of utility information. They provide utility stakeholders an efficient way to coordinate, manage utility relocation processes through improved visualization and communication with a reduction in delays and conflicts. Originality/value: Limited efforts were made using 3D BIM for sub-surface utility infrastructure in visualization and management of utility information. Efforts using 4D BIM in coordination and management of utility projects are left unexplored. This study adds value to the current literature through the application of 4D BIM for utility relocation projects.